Radar Polarimetric Interferometry Theory for Retrieval of Sea Ice Elevation - Nghiem, Son (IEEE DataPort, 2022)
To measure sea ice elevation abover the local sea surface, a theory of polarimetric interferometry for both monostatic and bistatic radars is developed based on analytic solutions of Maxwell's equations, accounting for realistic and complicated properties of snow, sea ice, and seawater. This theory preserves phase information that is imperative for radar polarimetry and interferometry.  The symmetry group theory is utilized to identify and select appropriate terms pertaining to the retrieval of sea ice elevation.  Theoretical calculations compare well with field observations for rough and old sea ice encountered in the Operation-IceBridge and TanDEM-X Antarctic Science Campaign over the Western Weddell Sea.  The results show that the magnitude of rho, which is defined as the coefficient of normalized correlation between co-polarized horizontal and co-polarized vertical radar returns, is inversely related to sea ice elevation while the associate phase term is nonlinear and noisy and should be excluded.  Both theoretical results and experimental data are included in the IEEE Dataport.